PERANCANGAN VIRTUAL REALITY DALAM MENGETAHUI GEJALA ACROPHOBIA - Muhammad fadli Prathama; Dwina Kuswardani; Andi Dahroni (Sekolah Tinggi Teknik - PLN, 2019)
The most common phobia in the entire world is Acrophobia (fearing heights), there are about 23% of the population stating that they are afraid of heights. Acrophobia sufferers will always look anxious and in a panic where the closest people need to be around to calm down. Excessive fear of anything is generally not good because it can hinder daily activities. So from that it is necessary to know the symptoms of acrophobia sufferers for the surrounding community to be able to take action to calm sufferers when sufferers of acrophobia relapse. The results of this study are expected to create a virtual reality-based software prototype to help people better recognize the symptoms of acrophobia sufferers. Researchers sincerely hope that the results of this study more or less provide benefits specifically for researchers and generally for all communities. This study is using the Multimedia Development Life Cycle (MDLC) method in software development